2018
DOI: 10.1016/j.dib.2018.08.180
|View full text |Cite
|
Sign up to set email alerts
|

Data on aluminum concentration in drinking water distribution network of rural water supply in Sistan and Baluchistan province, Iran

Abstract: The aim of this study is to determine the Aluminum concentration in groundwater resources of Sistan and Baluchestan province, Iran. See the data in this article. For the purpose of this study, a total of 871 water samples were collected and values of quality parameters including pH, turbidity, total dissolved solids (TDS) and Aluminum concentration were measured (with two-time repetitions) according to Standard Methods for the Examination of Water and Wastewater, during the year 2016. The mean, maximum, minimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
0
4
0
1
Order By: Relevance
“…Hospital effluent (min.-max.) Iran n.q 0.0004-0.059 n.q n.q (Akbari et al, 2018) Iran n.q n.q 0.005-3.3 n.q (Shakerkhatibi et al, 2019) Malaysia 0.11-0.12 n.q n.q n.q (Dzulfakar et al, 2011) Mexico n.q 0.06-62.60 n.q n.q (Torres Guzmán et al, 2010) Mexico n.q 120-239 n.q n.q (García-Medina et al, 2010b) Mexico n.q 6.04-24.44 n.q n.q (Martínez-vieyra et al, 2017) Pakistan n.q 1.01-4.27 n.q n.q (Kazi et al, 2009) Peru n.q n.q 0.05-0.7 n.q (de Meyer et al, 2017) United States n.q-0.112 n.q n.q n.q (Krewski et al, 2007) n.q= not quantified…”
Section: J O U R N a L P R E -P R O O Funclassified
“…Hospital effluent (min.-max.) Iran n.q 0.0004-0.059 n.q n.q (Akbari et al, 2018) Iran n.q n.q 0.005-3.3 n.q (Shakerkhatibi et al, 2019) Malaysia 0.11-0.12 n.q n.q n.q (Dzulfakar et al, 2011) Mexico n.q 0.06-62.60 n.q n.q (Torres Guzmán et al, 2010) Mexico n.q 120-239 n.q n.q (García-Medina et al, 2010b) Mexico n.q 6.04-24.44 n.q n.q (Martínez-vieyra et al, 2017) Pakistan n.q 1.01-4.27 n.q n.q (Kazi et al, 2009) Peru n.q n.q 0.05-0.7 n.q (de Meyer et al, 2017) United States n.q-0.112 n.q n.q n.q (Krewski et al, 2007) n.q= not quantified…”
Section: J O U R N a L P R E -P R O O Funclassified
“…Among the polluting substances that may be present in the effluents from these industries, we highlight Al, Fe, Zn, and Cd. Akbari et al 42 found Al levels of approximately 0.15 mg L -1 in drinking water from typically rural communities in the provinces of Sistan and Baluchistan in Iran. The WHO 40 recommends concentrations at or below 0.2 mg L -1 for drinking water; however, it is still possible that the percent of the total oral exposure to Al that results from contaminated drinking water may be less than 15%.…”
Section: Resultsmentioning
confidence: 99%
“…Water may contain aluminum from primary sources, due to leaching of rocks and soil (Water Quality Association, 2013). In a research performed by Akbari et al, (2018) , Iranian cities were mapping and mean, minimum and maximum aluminum concentrations of 0.015, 0.0004 and 0.059 mg.L -1 , respectively, were found in the water resources of the studied municipalities. However, none of these values was a problem.…”
Section: Watermentioning
confidence: 99%
“…In a similar study, analyzing water from lakes and rivers in Switzerland, (Peydayesh et al, 2019) found values between 10.4 and 100 ppb, or approximately 0.01 and 0.10 mg.L -1 . Although no sample has exceeded the recommended values, the mapping made it possible to identify the most critical areas relating to the contaminant potential, in addition to showing that the differences are possibly due to the natural characteristics of each region (Akbari et al, 2018;Peydayesh et al, 2019).…”
Section: Watermentioning
confidence: 99%